HUBUNGAN KADAR CA, ZN & FE SERUM PADA PASIEN TB DAN PASIEN TB RESIST OAT DI KOTA JAMBI - Aminahtun Latifah; Dewi Kurniasih; Muslina Muslina (Poltekkes Kemenkes Jambi, 2022)
Background: The highest tuberculosis (TB) morbidity and mortality rates are in developing countries, including in Indonesia. The nutritional status of TB sufferers is needed to assess the effectiveness of counseling in all health facilities. This study aims to determine the nutritional status, especially the Ca, Zn and Fe microelements in patients with TB and TB resistant to OAT. Methods: The study was conducted at 4 Community Health Centers in Jambi City. When the research will be carried out in 2021 using a cross-sectional research method. Secondary data is the status of the patient/respondent obtained from the health center where the respondent received treatment. Primary data were obtained through interviews and laboratory examinations on 25 respondents with non-OAT-resistant TB and 5 respondents with OAT-resistant TB. Examination of calcium, zinc and iron levels was carried out at the regional health laboratory in Jambi province. Results: Based on the results of the study, it was found that there were significant differences in iron levels between TB patients with OAT-resistant and non-resistant TB (p-value = 0.00). Meanwhile, no significant difference was found in Ca levels (p-value = 0.235) and Zn levels (p-value = 0.92). Conclusion: There is a significant difference in iron levels between TB patients and OAT-resistant TB. While the levels of calcium and zincid not experience a significant difference